Mother’s Knowledge and Family Income and the Frequency of Stunting Incidents - Nilasari Ardhyanti Sutanto; Iriani Ismail (Edumaspul: Jurnal Pendidikan, 2023)
Stunting is a condition where a toddler's height or body length is not appropriate when compared to his age. According to WHO, the factors causing stunting are family and household factors, giving breast milk, giving complementary foods to breast milk, and a history of infection. One of the influencing family factors is parents' lack of knowledge about nutrition and health. Another factor that causes stunting is family income. If access to food at the first level is disrupted, especially due to poverty, stunting will arise due to unaffordability in fulfilling daily nutrition. The aim of this research is to determine the relationship between maternal knowledge and family income on the incidence of stunting. The method used in this research is quantitative with a cross sectional approach, the population of this study is mothers who have children under 5 years in Paterongan Village, Galis District, Bangkalan Regency. The sample was 33 people. The instrument used is a questionnaire. The results of this study show that there is a significant relationship between maternal knowledge and a reduction in the incidence of stunting, p value 0.000. And there is a relationship between family income and a reduction in the incidence of stunting, p value 0.011.